2007
DOI: 10.1016/j.ecoenv.2005.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Crucian carp (Carassius carassius) VTG monoclonal antibody: Development and application

Abstract: The vitellogenin (VTG) in fish has been used as an important biomarker for monitoring endocrine disrupting compounds (EDCs). This paper reports the development of a new monoclonal antibody (McAb) against the VTG of crucian carp (Carassius carassius). The McAb has a molecular weight of 149.4 kDa (heavy chain: 53.1 kDa; light chain: 21.6 kDa), and double diffusion indicated that it belongs to the IgG1 subclass. The titer is 10 5 -10 6 and the affinity constant (K aff ) is 7.0 Â 10 8 L/mol, showing the high speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Blood plasma was assayed for VTG concentration using the previously validated, sandwich enzyme‐linked immunosorbent assay [22]. Briefly, the polyclonal antibodies against crucian carp VTG (c‐VTG) were coated on a 96‐well microtiter plate for a night at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood plasma was assayed for VTG concentration using the previously validated, sandwich enzyme‐linked immunosorbent assay [22]. Briefly, the polyclonal antibodies against crucian carp VTG (c‐VTG) were coated on a 96‐well microtiter plate for a night at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, VTG analysis was used to evaluate the estrogenic activities of secondary effluent and reclaimed water from the Gaobeidian STP (G‐STP) in Beijing (China). Crucian carp ( Carassius carassius ), a common Chinese species, was exposed to the secondary effluent and reclaimed water treated with the conventional process, and the plasma VTG level was analyzed using an enzyme‐linked immunosorbent assay [22]. For comparison, the estrogenic activities of the secondary effluent and reclaimed water also were evaluated using the recombinant yeast assay.…”
Section: Introductionmentioning
confidence: 99%
“…4), which indicates that the regulation of the adrenergic agents on zebrafish vtgAo1 expression is not estrogen signaling dependent. Previous studies have shown that the VTG molecule is highly conserved within the same family, and the cross-reactivity of antibody was detected in cyprinids such as the rare minnow, zebrafish, and carp (Tyler et al, 1996;An et al, 2007). Significant induction of the circulating vtgAo1 level by the MOXI was detected in the plasma with the carp Vtg ELISA Kit, even with the presence of TAM (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Although, some subunits of Vtgs are highly conserved and share a common general structure among fish (Finn, 2007), its complexity due to posttranslational modifications and translocation processes, often results, in poor antigenic cross-reactivity, even between closely related species (Watts et al, 2003;An et al, 2007). This makes a necessary more in-depth study of Vtg for every species of fish.…”
Section: __________________mentioning
confidence: 99%